PHARMACOEPIDEMIOLOGICAL MONITORING OF ANTIDEPRESSANT USAGE IN PATIENTS WITH ANXIOUS AND DEPRESSIVE SYNDROMES IN INTERNAL MEDICINE - N. V. Ivanova; B. B. Fischman; G. I. Schwartsman; L. A. Fomenko; A. A. Abdulin; M. S. Kazymov; I. V. Samsonova; M. A. Bobyr (Столичная издательская компания, 2015)
Aim. To study antidepressant usage in treatment of anxious and depressive disorders in real internal medicine practice. Material and methods. Retrospective analysis of 290 charts of patients, which were observed in Pskov region hospital from 2004 to 2005 was held. All patients suffered from different internal diseases and were treated with antidepressants because of anxious and depressive concomitant disorders. Results. Arterial hypertension observed in 28% of patients, ischemic heart disease - in 20%, heart failure - in 14%, cerebrovascular and peripheral nervous system diseases - in 18% and gastroduodenal diseases - in 20% of patients. Amitriptyline took the first place (49%) among antidepressant prescriptions. Next antidepressants according to prescription popularity were paroxetine (22%) and tianeptine (12%). Rate of other antidepressant prescriptions were not higher than 5%. There were differences in antidepressant prescriptions between physicians of different specialties. Conclusion. Reasonable approaches should be used to choose antidepressants. Selective serotonin reuptake inhibitors have benefit for the therapy of concomitant anxious and depressive disorders due to their good tolerability. Nevertheless tricyclic antidepressants are essential in some clinical situations.